Development of transdermal patch preparations binahong leaf extract (Anredera cordifolia (Ten.) Steenis) and antihyperglycemia test in rats - Galang Pergiawan Ramadhan; Iis Wahyuningsih; Wahyu Widyaningsih (Pharmaciana, 2023)
Binahong leaves are plants that have great potential as antihyperglycemics, and have chemical content including triterpenoids, flavonoids, and saponins. However, the development of binahong leaves in pharmaceutical preparations is still very lacking. Objectives of this study are knowing the transdermal patch formulation of binahong leaf extract (BLE) produces good physical properties and the development of BLE transdermal patches with different extract concentrations may blood glucose lower (BGL) levels in glucose-induced mice. This study uses a single-layer patch because it has the advantage of being able to penetrate faster and is suitable for compounds that have solubility in polar solvents. The research began with the extraction of binahong leaves, then formulated a transdermal BLE patch using a formula that includes HPMC (polymer), glycerol (plasticizer), oleic acid (enhancer) and tween 80 (enhancer). Diabetic rats were divided into 4 groups of 6 rats, negative control group (glucose + placebo), positive control group (glucose + insulin), FI group (glucose+ transdermal patch BLE 30%), and FII group (glucose + transdermal patch BLE 47%). BGL measurements are carried out on the 0th, 3rd, 5th, and 7th days. The physical characterization carried out includes organoleptic, weight uniformity, thickness, pH, folding resistance, and moisture content, obtained FI and FII results that meet the requirements set out by each test standard. BGL (mg/dL) from day 1 to day 7 decreased in each group, positive control (68.8±3.76), negative control (112.5±6.89), FI (81.0±4.04), and FII (72.33±5.12). Based on the statistical results of the T-test on the physical evaluation of BLE transdermal patch preparations of FI and FII there were significant differences in weight and thickness uniformity, but there were no significant differences in pH, folding power, and humidity tests. The administration of a 47% BLE transdermal patch provides a faster but insignificant BGL reduction effect compared to the 30% BLE FI transdermal patch.